The dark personality of Peruvian mothers: comparisons according to sociodemographic variables - Celio-Pillaca, Jose; Ruiz, Sandra (Revista Estudios Psicológicos, 2026)
The role of a mother involves a series of functions, responsibilities, and demands to be fulfilled, for which healthy behavioral patterns are required. Conversely, there is the dark triad of personality, composed of the components of psychopathy, Machiavellianism, and narcissism. The present study aimed to compare the personality traits of the dark triad among mothers in Metropolitan Lima and Callao according to their age, marital status, number of children, educational status of the children, and type of school management. The research approach was quantitative, with a non-experimental design and a comparative focus. The Dirty Dozen Dark Triad (DDDT) Scale was applied, and it was found that mothers with a single child scored higher in narcissism traits, while those with children enrolled in private schools presented higher scores in Machiavellianism traits. In conclusion, the results suggest adopting a prevention-oriented approach by psychologists, taking into account each context and the significant differences found in the study, as well as extending research on the dark triad in non-clinical populations, along with other sociodemographic variables and well-being factors.